2012
DOI: 10.1016/j.maturitas.2012.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Marital status, health and mortality

Abstract: Marital status and living arrangements, along with changes in these in mid-life and older ages, have implications for an individual's health and mortality. Literature on health and mortality by marital status has consistently identified that unmarried individuals generally report poorer health and have a higher mortality risk than their married counterparts, with men being particularly affected in this respect. With evidence of increasing changes in partnership and living arrangements in older ages, with risin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
193
3
7

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 270 publications
(219 citation statements)
references
References 31 publications
16
193
3
7
Order By: Relevance
“…In regard to total control measures during haze days, married participants were more likely to report higher usage of total control measures. This finding was in agreement with previous studies on health and mortality by marital status, which have consistently identified that unmarried individuals generally report less healthy behaviors and have a higher mortality risk than their married counterparts [19][20][21]. Younger age has been inversely associated with better health-related behavior [22,23].…”
Section: Discussionsupporting
confidence: 92%
“…In regard to total control measures during haze days, married participants were more likely to report higher usage of total control measures. This finding was in agreement with previous studies on health and mortality by marital status, which have consistently identified that unmarried individuals generally report less healthy behaviors and have a higher mortality risk than their married counterparts [19][20][21]. Younger age has been inversely associated with better health-related behavior [22,23].…”
Section: Discussionsupporting
confidence: 92%
“…Marital status is a key determinant of health and it is widely acknowledged that married individuals report better health outcomes and a lower risk for mortality than those who are not married, particularly men. 46 Just over half of those in our study were married or in a common-law relationship, which is slightly higher than those found in other Canadians studies. 38,39 It is worth noting that these other studies further demonstrate that those with mood and anxiety disorders were less likely to be married or in a commonlaw relationship than those unaffected by these disorders.…”
Section: Discussioncontrasting
confidence: 67%
“…This is in line with findings of Wang et al (2011), which suggest that exercise has a preventive impact on depression, especially among divorced, separated and widowed women. In general, single middle-aged and older adults have poorer health than their married counterparts (Robards et al 2012); hence the health-promoting impact of exercise may be more important to them. Area of residence did not show any moderator effects.…”
Section: Discussionmentioning
confidence: 99%